MAKNA PUISI HARU NO UTA KARYA SHINPEI KUSANO: KAJIAN SEMIOTIKA RIFFATERRE - Ni Putu Diah Tirta Ningsih; Ni Wayan Meidariani (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2025)
Abstract This study aims to determine the meaning contained in the poem